Technology preferences and routines for distributed families coping with a chronic illness - Pang, Carolyn E. (Simon Fraser University, 2013)
Most family members want to stay aware of each other's activities on an ongoing basis to maintain a sense of connectedness. In situations where a family member is ill, the desire to stay connected increases, as many families face the challenges of coping with the diagnosis and treatment of a chronic illness. Previous research has evaluated technologies designed to support patients and caregivers with personal health information management and sharing. However, we still do not have a detailed understanding of which technologies are preferred and what challenges people still face when sharing information with them. To address this problem, this thesis reports on a mixed-method study that explores technology preferences and health information sharing routines of distributed families coping with a chronic illness. The aim of these studies was to explore the nuances of technology selection and usage in such situations. The findings illustrate the reasons why people choose certain technologies over others, the ways in which they use them, and the challenges they face. Findings also point to the need for tools that mediate sharing health information across distance and age gaps, with consideration to respecting patient privacy and supportive roles while sharing such information.
Keywords: Intuitive interaction; whole body systems; conceptual metaphors; interaction design; mixed-method experiment; Riecke; Riecke_2013; Riecke_supervised_thesis; SIAT; alissa-antle; bernhard-riecke; carolyn-pang; supervisedThesis; thesis